2006
DOI: 10.4103/0028-3886.25144
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus aviumcerebellar abscess

Abstract: A Figure 2: (A) Saggital T2 sequence showing resolution of epidural hematoma. (B) Axial T1 (Fat sat) sequence showing resolution of hematomacompressing the spinal cord. [4] Methylprednisolone has been used occasionally with good results and its beneficial effects evolve around the membrane-stabilizing effect and the ability to suppress lipid perioxidation and hydrolysis and inflammatory chain reaction at the injury site. [5]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…9 One year later, and in the same country, a case of cerebellar abscess by this pathogen was described in a 5-year-old child with a history of otitis during the 3 previous years. 10 This would make our case the third one described in the literature, and we believe that its treatment could be used as an example for future cases. Our management, employing antibiotic and early surgical treatment, has been aggressive at all times.…”
Section: Discussionmentioning
confidence: 78%
“…9 One year later, and in the same country, a case of cerebellar abscess by this pathogen was described in a 5-year-old child with a history of otitis during the 3 previous years. 10 This would make our case the third one described in the literature, and we believe that its treatment could be used as an example for future cases. Our management, employing antibiotic and early surgical treatment, has been aggressive at all times.…”
Section: Discussionmentioning
confidence: 78%
“…Out of the sixteen cases, almost half of them presented a neurologic complication due to this bacterium: brain abscess or bacterial meningoencephalitis. We found three cases of brain abscess involving the temporal lobe and two cases of cerebellum abscess [36][37][38][39][40]. The association of chronic otitis media is common for all these cases.…”
Section: Enterococcus Aviummentioning
confidence: 77%
“…In the literature search we found only two cases of brain abscess due to E. avium. Mohanty et al (3,4) described two cases with chronic ear infection and reported that the chronic ear infection was the predisposing factor for occurrence of the brain abscess due to E. avium. The first patient died due to insufficient treatment, yet the other case recovered completely by effective treatment.…”
Section: Brain Abscess Is a Focal Suppurative Process Within The Braimentioning
confidence: 99%